Penerapan Inovasi Produk Dalam Meningkatkan Daya Saing Mie Pedas Meleleh Gunung Pangilun Kota Padang - Adiprana Mahendra; Mutiara Dela; Danda Febrizal; Sigit Sanjaya (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to enhance the competitiveness of the "Mie Pedas Meleleh" business in Gunung Pangilun, Padang City, through product innovation implementation. The challenges faced by the partner include limited product variations, weak brand identity, and suboptimal digital marketing. Activities were conducted through participatory-based socialization and training for the business owner. The results showed the development of new product variants, improved packaging quality, and increased knowledge and skills in branding and digital marketing. The implemented product innovation successfully attracted the younger market and opened opportunities for market expansion through digital platforms. This activity is expected to serve as a sustainable innovation-based development model for MSMEs.